(3GdSQGL GdefjQ aj GdEYGfI Ydi eYQaI HYV eYGfi cdGe QHfG GdMcje GdNHjQs - (3eMeO Hf CMeO GdTQHjfj, TeS GdOjf ; GdNWjH GdTQHjfj,J (B977 (3g` s
(3ChdgG (B:s
(3jHOC HJaSjQ ShQI GdCMRGH s
(3BNQgG (B:s
(3hgPG BNQ eG jSQg Gddg JYGdi ef GdSQGL GdefjQ hcGf GdaQGZ ef Pdc jhe GdCKfjf GdeHGQc KGdK YTQ UaQ GdNjQ ef TghQ SfI KeGfjI hSJjf hJSYeGFg ef GdgLQg GdfHhjI hGdMeO ddg QH GdYGdejf s
(3YdjgG Jedc eMeO GdTjHi aGJM HjJ Gddg GdMQGes
(3hJedc YHO Gddg Hf YeQ Hf CHj HcQ Hf jMji HGYdhi SfI (B1255(3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs